Madrasah dan Ujian Nasional (UN) - M. Imam Zamroni (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2009)
The policy of Final National Examination (UN) standardization has caused madrasah to become trapped in practical efforts to help students pass by focusing on repetitive practice of tests in the examination subjects. Learning was not a process of developing on maturing, but one of earning high test score and passing the UN. Ironically, the development of student potential was not a priority for the teaching-learning process as a result of the high importance given to test scores. The deification of test score and the application of the policy of standardization have resulted in the process of education causing fear in students. Finally, students experience stress and depression due to fear of failing the UN. Therefore, the policy of standardization of passing grades in the UN must be changed to reflect the spirit of decentralization of passing grades in the UN must be changed to reflect the spirit of decentralization and regional autonomy and appreciation of diversity of school quality and capacity for teaching and learning. Data collection methods were in-depth interviews and document analysis.